1998
DOI: 10.1101/gad.12.15.2434
|View full text |Cite
|
Sign up to set email alerts
|

E1A signaling to p53 involves the p19ARFtumor suppressor

Abstract: The adenovirus E1A oncogene activates p53 through a signaling pathway involving the retinoblastoma protein and the tumor suppressor p19 ARF . The ability of E1A to induce p53 and its transcriptional targets is severely compromised in ARF-null cells, which remain resistant to apoptosis following serum depletion or adriamycin treatment. Reintroduction of p19 ARF restores p53 accumulation and resensitizes ARF-null cells to apoptotic signals. Therefore, p19ARF functions as part of a p53-dependent failsafe mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
466
3
9

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 575 publications
(497 citation statements)
references
References 53 publications
19
466
3
9
Order By: Relevance
“…Another consequence of E2F activation is the transcription of the MDM2 inhibitor p14/p19 ARF , leading to p53 accumulation and to the consequent induction of cell apoptosis (De Stanchina et al, 1998;Berk, 2005).…”
Section: Adenovirus Early-region 1amentioning
confidence: 99%
“…Another consequence of E2F activation is the transcription of the MDM2 inhibitor p14/p19 ARF , leading to p53 accumulation and to the consequent induction of cell apoptosis (De Stanchina et al, 1998;Berk, 2005).…”
Section: Adenovirus Early-region 1amentioning
confidence: 99%
“…Recent studies demonstrated that the ARF tumor suppressor inhibits cell cycle through p53-dependent and p53-independent mechanisms. [38][39][40][41][42][43] Moreover, ARF/p53 double-null B cells are more resistant to Myc-induced apoptosis than cells lacking ARF or p53 alone. 31 At face value, these results imply that the p53-independent ARF function might be selected against in MIF-KO Em-Myc B-lymphomas.…”
Section: Mif-deficient Lymphomas Contain P53 Inactivating Mutations Amentioning
confidence: 99%
“…One explanation for this is that while ARF is not induced by DNA damage, it still can potentiate p53-dependent DNA damage responses that occur in the setting of Myc-induced genomic instability. 32,41,42 Frequencies of p53 and ARF mutations in MIF-KO Em-Myc mice are summarized in Table 1. Considering that only 67% of MIF-KO Em-Myc mice developed tumors by the age of 6 months (Figure 1a (Figure 4a, b).…”
Section: Mif-deficient Lymphomas Contain P53 Inactivating Mutations Amentioning
confidence: 99%
“…As p53 plays an important role in the surveillance of oncogenic activity via p14 ARF -dependent and independent pathways (de Stanchina et al, 1998;Zindy et al, 1998), we examined whether p53 is involved in Bcl-2-mediated inhibition of MCF7 cell proliferation. Western blot analysis revealed that the p53 protein was more abundant in Bcl-2-positive cells of clones 27, 24 and 30 than in the Bcl-2-negative cells of clones 2 and 26 ( Figure 3a).…”
Section: Expression Of Bcl-2 Inhibits Mcf7 Cell Growthmentioning
confidence: 99%
“…Expression of oncogenic Ras, c-Myc, E1A, E2F1, v-Abl and/or bcatenin in normal cells activates p53, at least in part, via the p14/p19 ARF tumor suppressor (Serrano et al, 1997; de Stanchina et al, 1998;Palmero et al, 1998;Zindy et al, 1998;Cong et al, 1999;Dimri et al, 2000;Damalas et al, 2001). In contrast, in colorectal cancer, expression of b-catenin induces p53 stabilization independently of p14/p19 ARF (Damalas et al, 1999).…”
Section: Introductionmentioning
confidence: 99%